Analisis Indeks Kepuasan Masyarakat (IKM) terhadap Kualitas Pelayanan di Puskesmas Bandarharjo di Kecamatan Semarang Utara - Ningtyas, Rahayu; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2014)
Puskesmas Bandarharjo as one of a government agency that provide services to the public can be considered qualified if it is to provide services fast, right and true to his customers.This research using a design or descriptive quantitative research design that is mixed between qualitative with quantitative to measure public satisfaction towards Bandarharjo health center services at Semarang. Samples taken by accidental sampling with a sample of 150 respondents using the Public Satisfaction Index (HPI).The results showed that the overall performance quality of service to the community health center service users can be categorized GOOD Bandarharjo in Semarang with the acquisition of community satisfaction index of 74.30 is within the interval from 62.51 to 81.25 so it can be concluded that the service quality at Puskesmas Bandarharjo is GOOD service based on the calculation method used Customer Satisfaction Index by Cartesius diagram. Out of the 14 indicators being measured there are three performance indicators are not good, there are indicators of officer discipline, politeness and friendliness of the staff and the comfort of the environment . This research was conducted to answer two main problems, namely the measurement of service quality to the community health center Bandarharjo using HPI and dimensions of HPI that inhibits people's satisfaction with health services provided Bandarharjo health center.